Experimental critical qualitative inquiry: Disrupting methodologies, resisting subjects - Marn, Travis M.; Wolgemuth, Jennifer R. (Post-Qualitative Research and Innovative Methodologies, 2020)
Keywords: dept.cur; ⛔ No DOI found

Purposeful Entanglements: A New Materialist Analysis of Transformative Interviews - Marn, Travis M.; Wolgemuth, Jennifer R. (Qualitative Inquiry, 2017)
In this article, we explore transformative interviewing through the lens of new materialism. Rather than viewing transformation through a humanist perspective that centralizes a transcendent self, we draw upon Barad’s agential realism to reconsider transformation following the ontological turn. Thinking with agential realism, we engaged two interview studies, one on biracialism and one on masculinity, to demonstrate how the materiality of our interviews (e.g., research bodies, computer programs, questionnaires) intra-acted with our participants to both facilitate and hinder our attempts at transformation. We conclude by theorizing transformation as a type of purposeful entanglement that proceeds from the material-discursive intra-actions of our inquiries.
Keywords: dept.cur

The failures and possibilities of philosophy in the material world - Van Cleave, Jessica; Marn, Travis; Wolgemuth, Jennifer (International Review of Qualitative Research, 2025)
Keywords: Engineering; Engineering ethics; Epistemology; Philosophy; dept.cur

Manufacturing Trustworthiness in Qualitative Research as a Writerly and Readerly Accomplishment: Introduction to the Special Issue - Van Cleave, Jessica; Wolgemuth, Jennifer; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Construct (python library); Product (mathematics); Qualitative research; Space (punctuation); Theme (computing); Tinker; Trustworthiness; dept.cur; possibility; publication; scholarly writing; trustworthiness

On the sidelines of what works: scientifically based indifference - Wolgemuth, Jennifer R.; Marn, Travis M.; Sabnis, Sujay (International Journal of Research & Method in Education, 2021)
A team of systematic reviewers successfully completed a government-commissioned review of ‘what works to improve post-school outcomes for youth with disabilities’ in 2012. Despite its success, interviews with 10 review team members revealed dissatisfaction with the process and indifference to its outcomes. The purpose of our analysis was to examine how the systematic review process itself led to review team members’ feelings of indifference, resignation, and pessimism. Drawing on the writings of Henry Giroux, Gert Biesta, and Hanna Arendt that warn of the death of democracy and the rise of totalitarianism, we explored how the systematic review certification process, examinations, rules, and structures deadened democratic deliberation and critique necessary, we argue, to conducting good educational science. We end with a call for systematic reviews in education whose researchers, products, and processes remain ethically oriented to keeping democracy alive. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.cur; peer-reviewed

#scholar #famous #monster - Wolgemuth, Jennifer; Lester, Jessica; Guyotte, Kelly; Koro‐Ljungberg, Mirka; Marn, Travis (Educational Researcher, 2025)
Academic success is now coupled with social media engagement. Social media has become so normalized in the academy that absent a carefully curated social media presence, scholars risk being seen as unscholarly, unproductive, and unpopular. This article lays bare the pressures, mechanisms, and monstrosities of using social media to promote scholarship. We argue that the widespread adoption of social media outpaces critical attention to its ethics and wonder about the future of public scholarship and the monstrous scholarly selves we are becoming. Thinking of monstrosity, with Krecˇicˇ and Žižek, as the preontological domain that rests beneath society and constitutes alterity and otherness, we ask what kinds of #scholarfamousmonsters we want to be, become, and promote in the digital era.
Keywords: Aesthetics; Art; Epistemology; Law; Literature; Media studies; Monster; Philosophy; Political science; Psychology; Scholarship; Social media; Social psychology; Sociology; Wonder; dept.cur; peer-reviewed

Radical uncertainty is not enough: (In)Justice matters of post-qualitative research: - Wolgemuth, Jennifer R.; Marn, Travis M.; Barko, Tim; Weaver-Hightower, Marcus B. (International Review of Qualitative Research, 2021)
Keywords: dept.cur; peer-reviewed

Start here, or here, no here: introductions to rethinking education policy and methodology in a post-truth era - Wolgemuth, Jennifer R.; Koro-Ljungberg, Mirka; Marn, Travis M.; Onwuegbuzie, Anthony J.; Dougherty, Shaun M. (Education Policy Analysis Archives, 2018)
This special issue takes up urgent questions about how we education scholars might think and do policy and methodology in what has come to be known as the post-truth era. The authors in this special issue grapple with questions about the roles and responsibilities of educational researchers in an era in which research and policy have lost their moorings in T/truth. Collectively they reconceptualize educational research and policy in light of post-truths, anti-science sentiment, and the global rise of right-wing populism. At the same time we editors wonder whether post-truth is given a bad rap. Could post-truth have something productive to offer? What does post-truth open up for educational research and policy? Or, is the real issue of this special issue a collective despair of our own insignificance and obsolescence in the wake of post-truth. Whatever we editors and authors aimed to do, this special issue will not be heard by post-truth adherents and partisans. Perhaps its only contribution is encouragement to stay with the troubles of a post-truth era, even as we despair the consequences of our research and policy creations. © 2018, Arizona State University. All rights reserved.
Keywords: Education policy; Fake news; Methodology; Post-truth; dept.cur; peer-reviewed

Work/Think/Play/Birth/Death/Terror/Qualitative/Research - Wolgemuth, Jennifer R.; Rautio, Pauliina; Koro-Ljungberg, Mirka; Marn, Travis M.; Nordstrom, Susan; Clark, Adam (Qualitative Inquiry, 2018)
Inspired by work/think/play in qualitative research, we centered the idea of “play” in a qualitative research project to explore what proceeding from the idea of work/think/play might look like and accomplish. We pursued play in an experimental qualitative inquiry over dinner one night at the 2016 Annual Meeting of the American Educational Research Association. Our article centers on one work/think/play inquiry three of us conducted. Through a playful account of how play unfolded in our work/think/play inquiry that evening, we explore research play as generative, deadly, and censored in the context of neoliberalism and other terrors. We reflect on what (good) play does in qualitative research, what our work/think/play/birth/death/terror/qualitative/research accomplished, if anything. Maybe research play is vital, what keeps us fit to do critical qualitative research. Yet research play moves (well) beyond normative rules of much qualitative research. Is it worth the risk? Can we know? Even after?
Keywords: dept.cur